Oxygen sensitivity of anammox and coupled N-cycle processes in oxygen minimum zones. - Tim Kalvelage; Marlene M Jensen; Sergio Contreras; Niels Peter Revsbech; Phyllis Lam; Marcel Günter; Julie LaRoche; Gaute Lavik; Marcel M M Kuypers (PLoS ONE)
Nutrient measurements indicate that 30-50% of the total nitrogen (N) loss in the ocean occurs in oxygen minimum zones (OMZs). This pelagic N-removal takes place within only ~0.1% of the ocean volume, hence moderate variations in the extent of OMZs due to global warming may have a large impact on the global N-cycle. We examined the effect of oxygen (O(2)) on anammox, NH(3) oxidation and NO(3)(-) reduction in (15)N-labeling experiments with varying O(2) concentrations (0-25 µmol L(-1)) in the Namibian and Peruvian OMZs. Our results show that O(2) is a major controlling factor for anammox activity in OMZ waters. Based on our O(2) assays we estimate the upper limit for anammox to be ~20 µmol L(-1). In contrast, NH(3) oxidation to NO(2)(-) and NO(3)(-) reduction to NO(2)(-) as the main NH(4)(+) and NO(2)(-) sources for anammox were only moderately affected by changing O(2) concentrations. Intriguingly, aerobic NH(3) oxidation was active at non-detectable concentrations of O(2), while anaerobic NO(3)(-) reduction was fully active up to at least 25 µmol L(-1) O(2). Hence, aerobic and anaerobic N-cycle pathways in OMZs can co-occur over a larger range of O(2) concentrations than previously assumed. The zone where N-loss can occur is primarily controlled by the O(2)-sensitivity of anammox itself, and not by any effects of O(2) on the tightly coupled pathways of aerobic NH(3) oxidation and NO(3)(-) reduction. With anammox bacteria in the marine environment being active at O(2) levels ~20 times higher than those known to inhibit their cultured counterparts, the oceanic volume potentially acting as a N-sink increases tenfold. The predicted expansion of OMZs may enlarge this volume even further. Our study provides the first robust estimates of O(2) sensitivities for processes directly and indirectly connected with N-loss. These are essential to assess the effects of ocean de-oxygenation on oceanic N-cycling.